Relationship between critical thinking disposition and teaching efficacy among special education integration program teachers in Malaysia - Sulaiman, Tajularipin; Kuppusamy, Suresh Kumar; Mohd Ayub, Ahmad Fauzi; Abdul Rahim, Suzieleez Syrene (AIP Publishing, 2016)
This study aims to assess the level of critical thinking disposition and teaching efficacy among the Special Education Integration Programme (SEIP) teachers in Negeri Sembilan, Malaysia. The level of critical thinking dispositions and teaching efficacy in the SEIP were compared based on teaching experience and gender. The study also examined the relationship between critical thinking disposition and teaching efficacy at SEIP. The research adopted a quantitative survey approach. A total of 190 primary school teachers from the SEIP in Negeri Sembilan were selected using proportional sampling method. The instrument used in this study comprised of three sections; demography, critical thinking disposition and teaching efficacy. Descriptive and inferential statistics were used in the analysis. Analysis shows that the respondents have a moderate level of critical thinking disposition (M = 2.99, S.D = 0.160) and teaching efficacy (M = 3.01 S.D. = 0.128) was at a high level. For teaching experience, the analysis showed that thinking disposition of novice teachers (mean = 2.52, SD = .503) are significantly higher than experienced teachers (mean = 2.35, SD = .481, t = 2.244, p <.05). There was no significant difference between male and female SEIP teachers in critical thinking disposition and teaching efficacy. Findings also indicated that there is a significant positive moderate relationship (r = .477) between critical thinking disposition and teaching efficacy among SEIP teachers. This study suggests that critical thinking disposition and teaching efficacy play an important role to enhance the performance of SEIP teachers.